Geochemical Characteristics and Water Content of Melt Inclusions in the Tuff of the Tiaojishan Formation, Liujiang Basin - Huizhen ZHAO; Yong CHEN; Cong TU; Yanwei FENG (Yankuang ceshi, 2025)
Water, as the primary volatile component in magmatic systems, has a significant impact on the formation and evolution of magma. The Tiaojishan Formation igneous rocks in the Liujiang Basin are significant products of Yanshanian volcanic activity. Although previous studies have extensively explored their geochemical characteristics, the water content of the magma in the Liujiang Basin during Yanshanian volcanic activity remains unclear. Melt inclusions, which capture the original magmatic information, serve as the most direct samples for determining the water content of magma. Based on geochemical analysis, this study quantitatively determines the water content in melt inclusions using laser Raman spectroscopy with standard samples. The results show that the lower tuff samples of the Tiaojishan Formation are characterized by high Si and Al contents, enrichment in LILEs, depletion in HFSEs, enrichment in LREEs, and depletion in HREEs. The water content in melt inclusions reveals a range of 0.99% to 4.98%, with an average of 2.62%. These characteristics jointly indicate the water-enriched acidic magmatic activity during the early Tiaojishan period in this area. Combining the water content of melt inclusions with the large-scale volcanic eruptions in the stage, this study suggests that high water content in the magma enhanced the eruptive dynamics of the magmatic system, making it a contributing factor to the large-scale volcanic eruption. The BRIEF REPORT is available for this paper at http://www.ykcs.ac.cn/en/article/doi/10.15898/j.ykcs.202404030074.